2008
DOI: 10.1111/j.1365-2583.2008.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Over expression of a Cytochrome P450 (CYP6P9) in a Major African Malaria Vector, Anopheles Funestus, Resistant to Pyrethroids

Abstract: Anopheles funestus Giles is one of the major African malaria vectors. It has previously been implicated in a major outbreak of malaria in KwaZulu/Natal, South Africa, during the period 1996 to 2000. The re-emergence of this vector was associated with monooxygenase-based resistance to pyrethroid insecticides. We have identified a gene from the monooxygenase CYP6 family, CYP6P9, which is over expressed in a pyrethroid resistant strain originating from Mozambique. Quantitative Real-Time PCR shows that this gene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 20 publications
5
99
0
Order By: Relevance
“…In 2008, Amenya et al [31] found the CYP6P9 gene to be over-expressed in the egg and adult stages of a pyrethroid resistant laboratory strain (FUMOZ-R) originating from southern Mozambique. Wondji et al [32] identified a quantitative trait locus (QTL) associated with pyrethroid resistance in the same An.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, Amenya et al [31] found the CYP6P9 gene to be over-expressed in the egg and adult stages of a pyrethroid resistant laboratory strain (FUMOZ-R) originating from southern Mozambique. Wondji et al [32] identified a quantitative trait locus (QTL) associated with pyrethroid resistance in the same An.…”
Section: Discussionmentioning
confidence: 99%
“…funestus (Amenya et al, 2008). A partial sequence of CYP6P9 was used in Northern, dot blot and real-time PCR expression studies.…”
Section: Discussionmentioning
confidence: 99%
“…funestus, higher levels of CYP6P9 mRNA are found in pyrethroid-resistant strains than in pyrethroid-susceptible strains (Amenya et al, 2008;Wondji et al, 2009). Consequently, P450 may play a protective role against insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrethroid resistance in A. funestus from South Africa and southern Mozambique was subsequently shown to be mediated by a monooxygenase (P450) detoxification mechanism and no target site insensitivity was identified (Brooke et al, 2001;Wondji et al, 2007;Okoye, 2008). Recently, the molecular characterization of monooxygenase-based pyrethroid resistance in A. funestus was initiated (Amenya et al, 2005(Amenya et al, , 2008Wondji et al, 2007Wondji et al, , 2009Matambo et al, 2010). Amenya et al (2005) isolated the first 31 partial monooxygenase P450 sequences and subsequently reported that one of these, CYP6P9, was over-expressed in the egg and adult stages of a pyrethroid-resistant laboratory strain (FUMOZ-R) originating from southern Mozambique (Amenya et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the molecular characterization of monooxygenase-based pyrethroid resistance in A. funestus was initiated (Amenya et al, 2005(Amenya et al, , 2008Wondji et al, 2007Wondji et al, , 2009Matambo et al, 2010). Amenya et al (2005) isolated the first 31 partial monooxygenase P450 sequences and subsequently reported that one of these, CYP6P9, was over-expressed in the egg and adult stages of a pyrethroid-resistant laboratory strain (FUMOZ-R) originating from southern Mozambique (Amenya et al, 2008). Wondji et al (2007) identified a quantitative trait locus (QTL) associated with pyrethroid resistance in the same A. funestus strain and confirmed the increase in CYP6P9 transcription.…”
Section: Introductionmentioning
confidence: 99%